Analisis Yuridis Penegakan Hukum Perjudian Online di Desa Besilam, Langkat - Nasution, Chairuni; H. Ketaren, Abdurrahman; Kartika, Nana; Reza, M. Ridwan Alfa (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyse law enforcement against online gambling crimes in Besilam Village, Langkat Regency, from the perspective of criminalisation in criminal law. Although online gambling is regulated in the Criminal Code and the Electronic Information and Transactions Law, in practice, law enforcement at the local level still faces various obstacles. The method used is a legal-empirical approach with a descriptive-analytical framework. Data was collected through interviews with village officials, police, and community members, supplemented by literature reviews. The findings indicate that weak law enforcement is attributed to limited technological resources, low public legal awareness, and inadequate coordination among law enforcement agencies. From a criminalisation perspective, online gambling remains relevant for criminal prosecution, but its mitigation must be accompanied by preventive and educational approaches. This study recommends strengthening the capacity of officials, updating regulations to be more adaptive to digital crimes, and actively involving the community in building a legal culture that is anti-gambling.